2008
DOI: 10.1177/001440290807500101
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Turnover: Examining Exit Attrition, Teaching Area Transfer, and School Migration

Abstract: The purposes of this research were to quantify trends in three components of teacher turnover and to investigate claims of excessive teacher turnover as the predominant source of teacher shortages. Attrition and teaching area transfer rates were comparable in special and general education and increased substantially from 1991-1992 to 2000-2001. School migration was stable over years, but higher in special than general education. Although annual turnover was high and increased to 1 in 4 teachers (25.6%) by 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
181
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(200 citation statements)
references
References 11 publications
4
181
2
5
Order By: Relevance
“…Teacher attrition rates markedly vary in different parts of the world; research shows that they range between 12-28% annually (Boe, 2007;Boe, Cook & Sunderland, 2008;Ingersoll & Merrill, 2010;Luekens, Lyter & Fox, 2004, 3). Looking more closely, however, annual attrition rates actually range between 5-30% (Boe et al, 2008;Macdonald, 1999). The highest attrition rates are generally seen in less developed countries, while lower levels are found in developed countries.…”
Section: Turnovermentioning
confidence: 99%
See 3 more Smart Citations
“…Teacher attrition rates markedly vary in different parts of the world; research shows that they range between 12-28% annually (Boe, 2007;Boe, Cook & Sunderland, 2008;Ingersoll & Merrill, 2010;Luekens, Lyter & Fox, 2004, 3). Looking more closely, however, annual attrition rates actually range between 5-30% (Boe et al, 2008;Macdonald, 1999). The highest attrition rates are generally seen in less developed countries, while lower levels are found in developed countries.…”
Section: Turnovermentioning
confidence: 99%
“…Annual area transfer rates are reported to vary between 10-14% and migration rates range between 7-10% (Boe et al, 2008;Cascone, Osborn, & Parker, 2011, 44-45;Ingersoll, 2002). Similar to annual attrition rates, area transfer rates in Finland are relatively low (2.2%) (Aho et al, 2009).…”
Section: Turnovermentioning
confidence: 99%
See 2 more Smart Citations
“…This issue's authors present ideas for managing responsibilities: Special educators report that their many responsibilities are often conflicting and sometimes overwhelming. Researchers have suggested that this contributes to stress, burnout, turnover, and attrition, poor quality services and lower educational outcomes for students (Billingsley, 2003;Boe, Cook, & Sunderland, 2008). Teachers, teacher educators, and school administrators need to collaborate to help special educators manage and balance their responsibilities as they work to achieve important individual and societal goals.…”
mentioning
confidence: 99%